Interdisciplinary approaches to disability - Ellis, Katie 1978-; Garland-Thomson, Rosemarie; Kent, Mike; Robertson, Rachel (Interdiscplinary disability studies, 2019)
How can a deep engagement with disability studies change our understanding of sociology, literary studies, gender studies, aesthetics, bioethics, social work, law, education, or history? Interdisciplinary Approaches to Disability (the companion volume to Manifestos for the Future of Critical Disability Studies)identifies both the practical and theoretical implications of such an interdisciplinary dialogue and challenges people in disability studies as well as other disciplinary fields to critically reflect on their professional praxis in terms of theory, practice, and methods. Topics covered include interdisciplinary outlooks ranging from media studies, games studies, education, performance, history and curation through to theology and immunology. Perspectives are drawn from different regions from the European Union to the Global South with chapters that draw on a range of different national backgrounds. Our contributors who write as either disabled people or allies do not proceed from a singular approach to disability, often reflecting different or even opposing positions. The collection features contributions from both established and new voices in international disability studies outlining their own visions for the future of the field. Interdisciplinary Approaches to Disability will be of interest to all scholars and students working within the fields of disability studies, cultural studies, sociology, law history and education. The concerns raised here are further in Manifestos for the Future of Critical Disability Studies